Pemanfaatan Kapur dari Siput Hisap Terebralia palustris sebagai Zat Antibakteri, Pereduksi Amonia dan Kadar Air dalam Feses Ayam Broiler - Nahak, Handrianus K.; Sanam, Maxs U. E.; Telupere, Franky M. S. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
This research was conducted to observe the effects of chalk derived from the combustion of Terebralia palustris snail shells on the inhibition of Escherichia coli and Staphylococcus aureus bacteria, its ability to reduce ammonia levels and to decrease moisture content in broiler chicken faeces and litter. The experimental design used in this study was group randomized design (GRD), with a total sample of 100 broiler chickens. The treatment groups were divided into 5 groups with different chalk concentrations: P0 (0%), P1 (2.5%), P2 (5%), P3 (7.5%), and P4 (10%). The results indicated that the different chalk concentrations significantly reduced ammonia levels in the coop (P<0.05), significantly decreased litter and faeces moisture content (P<0.05), and significantly increased litter and faeces pH (P<0.05), however, the chalk did not have antibacterial activity against Escherichia coli and Staphylococcus aureus with an average inhibition zone of <10 mm except for Staphylococcus aureus at 10% chalk concentration (P4), which showed weak antibacterial activity with an average inhibition zone of 10.66 mm. The study concluded that the use of chalk derived from Terebralia palustris snails in broiler chicken maintenance positively impacts the reduction of ammonia levels, the decrease in litter and faeces moisture content, and the increase in litter and faeces pH, but does not demonstrate significant antibacterial activity.